Volume 3A: Coal, Biomass and Alternative Fuels; Cycle Innovations; Electric Power; Industrial and Cogeneration 2014
DOI: 10.1115/gt2014-27124
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Greenhouse Gas Emissions in the Power Industry Using Compressed Air Power Enhancement Technology in Gas Turbines

Abstract: Environmental and supply considerations are playing a pivotal key in the economics and operation rationale behind power generation. A once fossil-fuel dependent industry is embracing renewable sources, albeit slowed by technical and economic challenges. With gas turbines comprising a large part of the world’s electric generation pool, increasing the power output of the existing combined cycle plants and avoiding the use of less efficient peakers has the potential of reducing greenhouse gas emissions. Performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Dinc et al [34] introduced air inlet air cooling with a refrigeration system to the same gas turbine and obtained the normal ambient temperature power values with a PSFC improvement of 5.2% compared to the uncooled case. Additional studies on engine emissions can be found in the literature [35][36][37][38].…”
Section: Of 19mentioning
confidence: 99%
“…Dinc et al [34] introduced air inlet air cooling with a refrigeration system to the same gas turbine and obtained the normal ambient temperature power values with a PSFC improvement of 5.2% compared to the uncooled case. Additional studies on engine emissions can be found in the literature [35][36][37][38].…”
Section: Of 19mentioning
confidence: 99%